Cannabinoid Receptor Type 1 (CB1R) Expression in Limbic Brain Structures After Acute and Chronic Seizures in a Genetic Model of Epilepsy - Lazarini-Lopes, Willian; da Silva-Júnior, Rui M. P.; Servilha-Menezes, Gabriel; Do Val-da Silva, Raquel A.; Garcia-Cairasco, Norberto (Frontiers in Behavioral Neuroscience, 2020)
The endocannabinoid system (ECS) is an endogenous mechanism related to epileptic seizure control. The cannabinoid receptor type 1 (CB1R) is widely expressed in the brain, especially in forebrain limbic structures. Changes in CB1R expression are associated with epileptic seizures in animal models and humans. The Wistar Audiogenic Rat (WAR) strain is a genetic model of epilepsy in which animals develop epileptic seizures in response to intense (120 dB) sound stimulation. The acute audiogenic seizures (AS) are characterized by tonic-clonic seizures and hyperexcitability of brainstem sites, but during the chronic protocol of AS, called audiogenic kindling (AuK), the initially brainstem-dependent seizures give rise to forebrain-dependent limbic seizures, a process called limbic recruitment. The WAR strain presents several physiological alterations associated with seizure susceptibility, but the ECS has never been explored in this strain. Therefore, the aim of the present study was to characterize CB1R expression in forebrain limbic structures important to limbic seizure expression in WARs, the hippocampus and the amygdala. We also analyzed the effects of acute and chronic seizures on CB1R expression in WARs. Briefly, WARs showed increased CB1R immunostaining in the basolateral amygdala nucleus (BLA) and in several layers and regions of the dorsal hippocampus, when compared to control Wistar rats. Acute AS, as well as AuK, increased CB1R immunostaining in the dorsal hippocampus and amygdala of WARs. Our results suggest that the endogenous increase of CB1R immunostaining in limbic brain sites, such as the hippocampus and amygdala, can be associated with seizure susceptibility in WARs. Our results also suggest that CB1R expression in WARs can be affected by acute and chronic AS. The present study brings important information regarding CB1R and seizure susceptibility in WARs and supports the relationship between ECS and epilepsy.